2017
DOI: 10.1038/icb.2017.31
|View full text |Cite
|
Sign up to set email alerts
|

Lectin pathway factors in patients suffering from juvenile idiopathic arthritis

Abstract: Both complement activation and certain infections (including those with Yersinia sp.) may contribute to the pathogenesis of juvenile idiopathic arthritis (JIA). We investigated factors specific for the lectin pathway of complement: mannose-binding lectin (MBL), ficolins and MBL-associated serine protease-2 (MASP-2), in 144 patients and 98 controls. One hundred and six patients had oligoarticular disease and 38 had polyarticular disease. In 51 patients (out of 133 tested), Yersinia-reactive antibodies were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…High serum MBL level was reported to be associated with thrombocytopenia and seizure in patients with SLE [22], and serum MBL was reported to be positively correlated with Birmingham Vasculitis Activity Score in patients with antineutrophil cytoplasmic antibody-associated vasculitis [23]. In addition, serum ficolin-1 was positively correlated with disease activity in patients with rheumatoid arthritis (RA) [24] and juvenile idiopathic arthritis [25]. Upregulated mRNA levels of ficolin-1 in peripheral blood mononuclear cells, and a lot of ficolin-1-positive monocytes in the glomeruli in patients with microscopic polyangiitis have also been reported [26].…”
Section: Discussionmentioning
confidence: 99%
“…High serum MBL level was reported to be associated with thrombocytopenia and seizure in patients with SLE [22], and serum MBL was reported to be positively correlated with Birmingham Vasculitis Activity Score in patients with antineutrophil cytoplasmic antibody-associated vasculitis [23]. In addition, serum ficolin-1 was positively correlated with disease activity in patients with rheumatoid arthritis (RA) [24] and juvenile idiopathic arthritis [25]. Upregulated mRNA levels of ficolin-1 in peripheral blood mononuclear cells, and a lot of ficolin-1-positive monocytes in the glomeruli in patients with microscopic polyangiitis have also been reported [26].…”
Section: Discussionmentioning
confidence: 99%
“…Ficolin-3 is encoded by the FCN3 gene which is located on chromosome 1p36 and contains eight exons. Few studies showed an association between collectin and colin genes polymorphisms and infectious and autoimmune diseases [31][32][33][34][35][36]. It was shown that there are some associations between gene polymorphisms of MBL [37][38][39][40], Ficolin-1 [16], Ficolin-2 [41] [42], and MASP-2 [43] with RF.…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing body of evidence that inadequately controlled activation of complement factors leading to either overactivity or deficiency may be involved in the pathogenesis of some autoimmune diseases [36]. However, the role of the complement system in JIA is still not fully elucidated [7–11]. Most studies involve investigations of the classical and the alternative pathway and have shown contradictory results [7, 9, 1214].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the remaining lectin pathway proteins in JIA are scarce [11, 24]. In 2015, Petri et al [24] compared the lectin pathway protein levels in patients with oligoarticular and systemic JIA (sJIA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation